The lichen genus Stereocaulon in Antarctica and South Georgia - Smith, Ronald I Lewis; Øvstedal, Dag Olav (Polar Biology, 1991)
Six species of Stereocaulon and one unnamed taxon (close to S. glabrum) are reported from South Georgia, the maritime Antarctic islands and Antarctic Peninsula. S. caespitosum is new to the western sub-Antarctic. Variations in morphology and secondary chemistry are provided, and the ecology and geographical distribution in the sub-Antarctic and Antarctic biomes are given for each taxon.
Keywords: Antarktis; botanikk; lav; planter